High-Throughput Sequencing Discloses the Cucumber Mosaic Virus (CMV) Diversity in Slovakia and Reveals New Hosts of CMV from the Papaveraceae Family - Mrkvová, Michaela; Hancinsky, Richard; Predajna, Lukas; Alaxin, Peter; Achs, Adam; Tomasechová, Jana; Soltys, Katarína; Mihálik, Daniel; Olmos, Antonio; Ruiz-García, Ana B.; Glasa, Miroslav (MDPI, 2022)
Cucumber mosaic virus (CMV; Cucumovirus, Bromoviridae) is an omnipresent virus characterized by a large host range and high genetic variability. Using high-throughput sequencing, we have characterized near complete genomes of 14 Slovak CMV variants from different plant hosts. Of these, three variants originated from the Papaveraceae species (oilseed poppy, common poppy and great celandine), previously poorly described as CMV natural hosts. Based on a BLAST search and phylogenetic analysis, the Slovak CMV isolates can be divided into two genetically different Groups, Ia and II, respectively. The SL50V variant, characterized by a divergent RNA2 sequence, potentially represents a reassortant variant. In four samples (T101, SL50V, CP2, MVU2-21), the presence of satellite CMV RNA was identified along with CMV. Although mechanically transmitted to experimental cucumber plants, the role of satellite RNA in the symptomatology observed could not be established due to a complex infection of original hosts with different viruses.